1990
DOI: 10.1128/aac.34.11.2217
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of tubercle bacilli in cultured human macrophages by chloroquine used alone and in combination with streptomycin, isoniazid, pyrazinamide, and two metabolites of vitamin D3

Abstract: Intracellular tubercle bacilli (TB) reside in vacuoles in infected human macrophages (MPs). The Tubercle bacilli (TB) in infected human macrophages (MPs) reside in vacuoles (4). These vacuoles might be phagolysosomes, which would be acidic and have several acid-dependent enzymes and activities (18). The presumed vacuolar acidity is thought to affect the activities of certain anti-TB drugs. It is supposed to decrease that of streptomycin (SM) (7) and increase that of pyrazinamide (PZA) (21,22,27).Chloroquine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 19 publications
(48 reference statements)
3
31
0
Order By: Relevance
“…Within endosomes, the acidic pH of the vacuole leads to its protonation and the protonated form of chloroquine gets trapped within endosomes (41). This concentrated chloroquine can kill bacteria within the phagocytic vacuole without any effect on cytosolic bacteria (7,10,26,35). We have shown that curcumin treatment prevents the escape of cytosolic bacteria, Shigella flexneri and Listeria monocytogenes, probably by stabilizing the endosomal membrane.…”
Section: Curcumin Modulates Fate Of Intracellular Bacteriamentioning
confidence: 86%
See 1 more Smart Citation
“…Within endosomes, the acidic pH of the vacuole leads to its protonation and the protonated form of chloroquine gets trapped within endosomes (41). This concentrated chloroquine can kill bacteria within the phagocytic vacuole without any effect on cytosolic bacteria (7,10,26,35). We have shown that curcumin treatment prevents the escape of cytosolic bacteria, Shigella flexneri and Listeria monocytogenes, probably by stabilizing the endosomal membrane.…”
Section: Curcumin Modulates Fate Of Intracellular Bacteriamentioning
confidence: 86%
“…The survival assay was performed as described previously with some modifications (6,9). Briefly, overnight cultures of methicillin-resistant S. aureus (MRSA; strain COL) were diluted to 10 5 CFU in Mueller-Hinton medium. NaNO 2 and H 2 O 2 were freshly prepared at 200 mM, 1 mM, and 2 mM.…”
mentioning
confidence: 99%
“…Thus, the likelihood of resistance developing should be relatively small. Moreover, chloroquine may be beneficial for other intracellular pathogens that affect individuals with impaired cell-mediated immunity, as experimental data with several of these pathogens suggest (4)(5)(6)46). However, because chloroquine can interfere with effective antigen-processing (47), the greatest benefit might be in those patients with severely impaired T cell function, particularly individuals with AIDS and CD4ϩ T cell counts Ͻ 100/l blood.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, chloroquine inhibits the growth ofMycobacterium tuberculosis in human MO and also significantly enhances the effectiveness of isoniazid and pyrazinamide against intracellular M. tuberculosis (43).…”
Section: Discussionmentioning
confidence: 99%